The Impact of Surgical Technique on Recurrence Rates After Inguinal Hernia Repair: a Retrospective Analysis - Isabela Olga (Journal of Social Research, 2023)
Inguinal hernia repair is a common surgical procedure to treat the condition of inguinal hernia, which is the escape of internal organ tissue through a gap or weakness in the lower abdominal wall. After undergoing surgery, the recurrence rate of inguinal hernia may vary. Therefore, it is important to conduct a retrospective analysis to understand the impact of surgical techniques on inguinal hernia recurrence rates. The aim of this study was to analyze the impact of surgical techniques on the recurrence rate of inguinal hernia. This study used a retrospective analysis method. Data were collected from questionnaires and medical records of patients who had undergone inguinal hernia repair surgery at X hospital. The data obtained included information about the surgical technique used, patient characteristics, such as age and gender, and the rate of recurrence of inguinal hernia that occurred after surgery. The collected data will be statistically analyzed using the IBM SPSS program. The results showed that surgical techniques with laparoscopic methods have a lower inguinal hernia recurrence rate than conventional methods. This can be seen from the results of the regression coefficient test with a recurrence rate of 28.7% compared to the conventional method of 32.6%.